2019
DOI: 10.31234/osf.io/c65wm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Powerful Moderator Variables in Behavioral Science? Don’t Bet on Them (Version 3)

Abstract: The current upsurge of interest in research replicability (and the exposure of many failures of reproducibility) has led to a much discussion about the possible role of statistical moderation (i.e., variable × variable interactions) in behavioral and social science. These interactions are so widespread and powerful, it is often argued, that we should hardly be surprised when attempts to reproduce important findings frequently lead to failure. Prior literature provides little empirical evidence about how common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 32 publications
4
24
0
Order By: Relevance
“…However, I expect that the performance is similar for three or more groups, as long as the sample size in each group remains constant. The effect sizes for group differences (or moderation effects) are typically small in observational behavioral datasets (e.g., Sherman & Pashler, 2019;Chaplin, 1997;McClelland & Judd, 1993). The true effect sizes are therefore likely to be close to θ = 0.05 or θ = 0.15 for Gaussian and Ising models, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, I expect that the performance is similar for three or more groups, as long as the sample size in each group remains constant. The effect sizes for group differences (or moderation effects) are typically small in observational behavioral datasets (e.g., Sherman & Pashler, 2019;Chaplin, 1997;McClelland & Judd, 1993). The true effect sizes are therefore likely to be close to θ = 0.05 or θ = 0.15 for Gaussian and Ising models, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These trials feature large samples of students within schools randomly assigned to condition (12,486 and 26,406, respectively), large numbers of school sites intentionally sampled to permit cross-site comparisons (65 and 21, with the latter further divided into 365 Race × First-Generation Status × College × Cohort groups), and preregistered hypotheses and analyses. Such precautions are necessary because heterogeneity findings can be unreliable (Bloom & Michalopoulos, 2013), especially with small samples (Sherman & Pashler, 2019). Moreover, each intervention was homogenously persuasive across sites, as assessed by manipulation checks.…”
Section: Vulnerability and Opportunitymentioning
confidence: 99%
“…More recently, Sherman and Pashler (2019) estimated the magnitude of interactions between person and environment variables in five studies, with 42 to 542,700 effects per study. The averaged incremental Rs (computed across all possible models within each study) beyond the main effects of the person and environment variables ranged from .019 to .131 for those five studies.…”
Section: Effect Patternsmentioning
confidence: 99%
“…For person-environment relations, previous empirical research has shown that distinguishing between 18 And unfortunately likely also even within this very chapter! 19 I thank Gabriela Blum for bringing up this idea in a personal email communication (May, 2019).…”
Section: Theory Multidisciplinary Integration Replication and Collaborationmentioning
confidence: 99%